2022
DOI: 10.3389/fncel.2022.848764
|View full text |Cite
|
Sign up to set email alerts
|

Pericyte Loss Leads to Capillary Stalling Through Increased Leukocyte-Endothelial Cell Interaction in the Brain

Abstract: The neurovascular unit is a functional unit composed of neurons, glial cells, pericytes, and endothelial cells which sustain brain activity. While pericyte is a key component of the neurovascular unit, its role in cerebral blood flow regulation remains elusive. Recently, capillary stalling, which means the transient interruption of microcirculation in capillaries, has been shown to have an outsized impact on microcirculatory changes in several neurological diseases. In this study, we investigated capillary sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 67 publications
6
19
0
Order By: Relevance
“…Flow stalls are typically seen in only 0.4% of brain capillaries of healthy adult mice, and an increase to 1.8% in a mouse model of AD was associated with worsened cognitive performance 36 . In agreement with this idea, a recent study using an adult-induced genetic pericyte depletion model also observed increased capillary stalling 43 . This effect was attributed to enhanced leukocyte–endothelial interaction, but may also involve flow steal in capillary networks.…”
Section: Discussionsupporting
confidence: 65%
“…Flow stalls are typically seen in only 0.4% of brain capillaries of healthy adult mice, and an increase to 1.8% in a mouse model of AD was associated with worsened cognitive performance 36 . In agreement with this idea, a recent study using an adult-induced genetic pericyte depletion model also observed increased capillary stalling 43 . This effect was attributed to enhanced leukocyte–endothelial interaction, but may also involve flow steal in capillary networks.…”
Section: Discussionsupporting
confidence: 65%
“…In a second approach, only diphtheria toxin is genetically expressed in mural cells, including pericytes. This approach also leads to marked loss of pericytes with widespread blood flow deficits and tissue hypoxia, but there is a surprising lack of BBB dysfunction (Park et al, 2017;Choe et al, 2022). This discrepancy may be due to off-target effects of the toxin provided systemically, though more studies are needed.…”
Section: Introductionmentioning
confidence: 99%
“…36 In agreement with this idea, a recent study using an adult-induced genetic pericyte depletion model also observed increased capillary stalling. 43 This effect was attributed to enhanced leukocyte-endothelial interaction, but may also involve flow steal in capillary networks.…”
Section: Discussionmentioning
confidence: 99%